The Byzantine Office of Ἐπὶ τῶν κρίσεων and Its Holders (in the Light of Sphragistic Evidence and Written Sources) - Symeon Antonov (Studia Ceranea, 2017)
The paper investigates the establishment of the office of the epi ton kriseon during the Reign of emperor Constantine IX Monomachos (1042–1055), analysing the reasons behind its creation and its initial character. In addition, a list of all holders of this office is provided, based on all available sources – sphragistic, epistolary, rhetorical, documentary, etc. The list is divided into two parts – before and after the sack of the Byzantine capital by the Crusaders in 1204. Certain conclusions are reached at the end of the paper based on the data from the first part of the list. Different aspects of the problem are examined, including the honorific titles of the epi ton kriseon, their other offices, activities and social bonds. Individuals who held this position include prominent figures such as Konstantinos, nephew of patriarch Michael I Keroularios (1043–1058) and the addressee of many letters from Michael Psellos, as well as the 12th–13th century historian Niketas Choniates. In the 11th–12th century, these officials were an indelible part of the Byzantine bureaucratic elite and the Constantinopolitan society; they exerted their power not only in the capital, but also in the provinces.